Elderly Empowerment through the Karang Werda Wisanggeni Community in Cemandi Village, Sedati District, Sidoarjo Regency - Arif Maulana Susanto; Cindy Asli Pravesti; Hayu Della Nikmala; Isna Rohma Nia Wati; Kholishotul Amaliyah; Rahma Dwi Anggraini; Oktavia Syafa Non Tyas; Wahyu Illahi; Rama Maulana Kusherlambang; Achmad Shobirin Rizanto; Gilang Pratama Bintang; Bilqis Amiroh Azzah Aribah (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Karang werda wisanggeni is an association that was established in 2004 in the Cemandi Village area which is used to accommodate the activities of the elderly. The existence of this activity encourages the productivity of the elderly in self-development activities, in order to strengthen socio-economic functions. In addition, the empowerment of elderly centers at the age of 60 and over is a place for the elderly to be productive in order to increase life expectancy. The benefits of having karang werda wisanggeni elderly are as a shelter, guidance, and an elderly integrated health service post. The dedication method is the title event by going through three stages, namely the preparation stage, the empowerment stage, and the closing stage. One of its forms is to create activities to commemorate Mother's Day by involving the elderly. The elderly performed Reog Cemandi art to commemorate Mother's Day. This opportunity is a form of increasing social welfare for the elderly. In essence, the elderly can play an active role in social life, so that the elderly can be more productive in increasing life expectancy. In the next service, you can actively involve the karang werda Wisanggeni elderly in Cemandi village.